Interactive Effects of Nutrients and Bradyrhizobium japonicum on the Growth and Root Architecture of Soybean (Glycine max L.) - Egamberdieva, Dilfuza; Jabborova, Dilfuza; Wirth, Stephan J.; Alam, Pravej; Alyemeni, Mohammed N.; Ahmad, Parvaiz (Frontiers in Microbiology, 2018)
Understanding the symbiotic performance of rhizobia and responses of plant root systems to mineral nutrient supply will facilitate the development of strategies to enhance effective rhizobia-legume symbioses. Interactive effect of nitrogen (N), phosphorus (P) and magnesium (Mg) on the symbiotic performance of soybean (Glycine max L.) with Bradyrhizobium japonicum, nodulation, root architecture and the N concentration in plant tissue under hydroponic conditions were studied. Plant growth was significantly higher under a high N supply combined with Mg (HNHMg) than in combination with P (HNHP), which was attributed to the interaction between N and Mg ions. The plants grown at a low N concentration combined with either high or low P or Mg (LNHP, LNHMg, LNLP, and LNLMg) showed a higher nodule dry weight compared to those grown under a high N supply. We observed that the N content in the roots and shoots of soybean plants was significantly lower under LNHP or LNLP, but it was higher under HNHMg or LNHMg, indicating that Mg promotes N acquisition by the plant tissues. Neither root nor shoot growth responded significantly to P availability regardless of the N supply. We observed significant positive relationships between the number of nodules, the N content in plant tissues and the root system architecture of soybean plants grown with a variable supply of Mg combined with N, which highlights the importance of N and Mg availability in the growth medium in regulating root system architecture and nodule formation. The number of rhizobial cells colonizing soybean roots was highest under the HNHMg treatment (6.78 × 104 CFUs/cm of root tip), followed by the HNLMg (4.72 × 104 CFUs/cm of root tip) and LNHMg (4.10 × 104 CFU/cm of root tip) treatments, and lowest under the LNLMg (1.84 × 104 CFUs/cm of root tip) nutrient conditions. The results of this study contribute to new insights for the improvement of the root system and the symbiotic performance of rhizobia inoculated on legumes, stressing the importance of a balanced supply of nutrients.